Exploring the Impact of Empowerment on Group Effectiveness: Multi-dimensional Social Network as the Mediating Variable - Lee, Su-Shiang; Peng, Tan Wei; Lee, Cheng-Feng; Lin, Chih-Wei (International Review of Management and Marketing, 2017)
The purpose of this research was aimed to explore the importance of fitness club employees’ management by using multi-dimensional social network point of view and use the method purpose by Preacher and Hayes (2008) to analyze the mediating effect of multi-dimensional social networks in empowerment and group effectiveness. The subjects of this study were employees from a well-known chain fitness club in southern of Taiwan. The results show that: The “meaning” and “competence” of employees’ empowerment can significant predict the social networks and group effectiveness; the “network centrality”, “social solidarity” and “social impact” of employees’ social networks can significantly predict group effectiveness; and the social network of fitness club employees has significant mediating effect between empowerment and group effectiveness. The “meaning” of empowerment has a low impact on group effectiveness, and has a moderate impact on group effectiveness through by social network; the “competence” of empowerment has no significant direct impact on group effectiveness, but also can influence group effectiveness through by social networks. According to the results of this study, practical strategies and recommendations were purposed. Keywords: Empowerment, Social Networking, Group Effectiveness JEL Classifications: M10, M14, M16